Optimizing Mobile App Performance: Best Practices for Developers - Pavan Surya Sai Koneru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Mobile app performance optimization is critical in today’s competitive marketplace where users expect instant responsiveness. This article explores essential techniques for improving app speed through lazy loading, efficient caching strategies, and optimized API calls. It examines memory and battery management approaches including proper resource handling, view recycling, and strategic background processing. The implementation of Mobile DevOps practices, featuring CI/CD pipelines with performance testing, analytics tools, and real user monitoring, provides developers with frameworks to ensure consistently high-quality user experiences across device types and geographical regions. By addressing these optimization areas systematically, developers can significantly enhance user satisfaction, retention, and engagement while reducing crashes, battery drain, and abandonment rates.